FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KEBERDAYAAN PETANI DALAM MENCAPAI DIVERSIFIKASI PANGAN - Asih Mulyaningsih; Andjar Astuti (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2021)
This research entitled Factors that influence Farmer Empowerment in Achieving Food Diversification. Food diversification is a food selection process that does not depend on just one type of food but rather on various types of food. The purpose of this study is to analyze the factors that affect the level of farmer empowerment and to analyze the level of farmer empowerment in realizing Food diversification. The population in this study were farmers of maize, cassava and sweet potatoes. The research locations were Munjul District, Menes District, and Angsana District, Pandeglang Regency, Banten Province. The research design used a quantitative approach involving 90 respondents. Respondents were determined by means of proportional random sampling based on the research criteria. Data were collected from February to April 2021. Data analysis used multiple linear regression. The results showed that the factors that affect the level of farmer empowerment are perceptual factors, supporting factors, and empowerment intensity factors. The level of farmer empowerment in his ability to make decisions and partner in realizing food diversification is high